Practices of Mother Tongue-Based Multilingual Education (MTB-MLE) Implementation in Paranas, Samar - Autor, Anazel (International Journal of Linguistics, 2025)
Purpose: This study explored the practices of Mother Tongue-Based Multilingual Education (MTB-MLE) implementation in Paranas, Samar. Methodology: Using an exploratory qualitative research design, data were gathered from key informant interviews with teachers who are implementing MTB-MLE. Findings: The findings revealed that using the mother tongue as the medium of instruction significantly improves comprehension and engagement among learners. Other best practices include contextualization, bridging of languages, reflecting cultural relevance, and promoting the expression of ideas. However, teachers encountered multiple challenges such as difficulties in translating technical terms, dialectal variation, limited learning materials, late distribution of resources, language confusion, insufficient teacher training, and inappropriate graphics in instructional tools. Unique Contribution to Theory, Practice and Policy: The study concludes that while MTB-MLE has transformative potential, it requires systemic support through localized resources, sustained training, and collaborative planning. A model of MTB-MLE implementation was proposed to institutionalize these best practices and overcome implementation barriers.